The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1046/j.1460-9592.2003.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of High Resolution Electrograms Memorized by DDDR Pacemakers in the Interpretation of Arrhythmic Events

Abstract: The accuracy of information retrievable from the memories of DDDR pacing systems has been limited by the absence of actual electrograms confirming the proper sensing of spontaneous cardiac activity versus that of extraneous signals. This study examined the diagnostic power of a new arrhythmia interpretation scheme, which includes the recording and storage of high resolution endocavitary atrial and ventricular electrograms (HREGM). HREGM stored in the memories of new generation pacemakers (PM) in response to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
1
9
0
2
Order By: Relevance
“…Israel et al confirmed AT in 35% (83 of 235) of stored mode switch episodes in 46 patients (Pulsar VDD, Guidant) 12 . Defaye et al reported appropriate detection of atrial arrhythmias in 34% of 206 stored episodes from 70 of 520 patients using a variety of devices (Guidant Discovery 1274, Pulsar 972, Pulsar Max 1270) 13 . Bordacher et al 14 reported inappropriate mode switch detection due to FFRW oversensing in 20% of 3,511 mode‐switch episodes from 137 patients (Talent DR213 PM, ELA Medical, Montrouge, France).…”
Section: Discussionmentioning
confidence: 99%
“…Israel et al confirmed AT in 35% (83 of 235) of stored mode switch episodes in 46 patients (Pulsar VDD, Guidant) 12 . Defaye et al reported appropriate detection of atrial arrhythmias in 34% of 206 stored episodes from 70 of 520 patients using a variety of devices (Guidant Discovery 1274, Pulsar 972, Pulsar Max 1270) 13 . Bordacher et al 14 reported inappropriate mode switch detection due to FFRW oversensing in 20% of 3,511 mode‐switch episodes from 137 patients (Talent DR213 PM, ELA Medical, Montrouge, France).…”
Section: Discussionmentioning
confidence: 99%
“…Current implantable pacemakers offer to the patients a better quality of life due to the existence of mathematical algorithms that aim to mimic the physiological behavior of the heart by individualized programming . They also provide the possibility of monitoring the patient’s cardiac rhythm through the intracavitary register of electrograms.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The 24 hour Holter is aim to mimic the physiological behavior of the heart by individualized programming. [6][7][8][9] They also provide the possibility of monitoring the patient's cardiac rhythm through the intracavitary register of electrograms. Some authors call them as "intelligent pacemakers," because of their more precise information storage, such as electrocardiographic telemetry and event markers and counters.…”
Section: Introductionmentioning
confidence: 99%
“…However, data on the proportion of patients who develop ATs during therapy with a dual chamber pacemaker show a striking discrepancy. While studies, which assessed the AT incidence on the basis of ECG recordings at scheduled or unscheduled follow‐up visits, report an annual incidence of 0.4–14%, 1,3,4 studies assessing the same endpoint based on pacemaker memory data report an incidence of 23–69% 5–9 . This may be due to the low sensitivity of serial ECG recordings, or due to the low specificity of pacemaker memory data which may count atrial sensing errors as AT.…”
Section: Introductionmentioning
confidence: 99%
“…While studies, which assessed the AT incidence on the basis of ECG recordings at scheduled or unscheduled follow-up visits, report an annual incidence of 0.4-14%, 1,3,4 studies assessing the same endpoint based on pacemaker memory data report an incidence of 23-69%. [5][6][7][8][9] This may be due to the low sensitivity of serial ECG recordings, or due to the low specificity of pacemaker memory data which may count atrial sensing errors as AT. Therefore, the precise incidence of ATs in patients with dual-chamber pacemakers remains to be determined and poses a therapeutic dilemma; for instance, regarding the need of anticoagulation therapy.…”
Section: Introductionmentioning
confidence: 99%